Clinical pharmacology and drug-drug interactions of lenvatinib in thyroid cancer. (July 2021) - Fogli, Stefano; Gianfilippo, Giulia; Cucchiara, Federico; Del Re, Marzia; Valerio, Laura; Elisei, Rossella; Danesi, Romano
Graphical abstract: Highlights: Lenvatinib is the first therapeutic option in patients with radioiodine-refractory differentiated thyroid cancer. Common adverse drug reactions can be managed by monitoring of patients, drug dose adaptation and/or specific therapy. No dose adjustment needed for mild-to-moderate hepatic/renal failure. No significant interaction with food or CYP3A4 inducers/inhibitors. Avoid combinations with clearly established QT prolongation agents or use drugs with no torsadogenic potential. Abstract: Lenvatinib is a non-selective tyrosine kinase inhibitor (TKI) with high in vitro potency against vascular endothelial growth factor receptors. Although this drug is used to treat several cancer types, it is the most effective TKI used in patients with thyroid cancer. Lenvatinib is well tolerated and the most common adverse drug reactions can be adequately managed by dose adjustment. Particularly, blood pressure and cardiac function monitoring, as well as antihypertensive treatment optimization, may be required in patients treated with lenvatinib. Dose reduction should be taken into account in patients with body weight <60 kg or severe hepatic failure. No significant change in lenvatinib pharmacokinetics has been observed with other patient-related factors and very few data are available on lenvatinib pharmacogenetics. Lenvatinib can be administered orally regardless of food and no clinically relevant drug-drug interactions have been reported.